A literature review of the epidemiology of sepsis in Latin America (2005)
ABSTRACT: Objectives. Epidemiological studies from the United States of America and from Europe have shown that sepsis is a widely prevalent syndrome, with either steady or slightly decreasing rates of morbidity and of mortality in recent decades. The objective of this paper is to provide a systematic review regarding the description and characterization of sepsis in Latin America. Methods. To locate materials on sepsis in Latin America, a comprehensive search strategy was employed with three medical bibliographic databases, using combinations of the terms “sepsis,” “septicemia,” “bacteremia,” “sepsis syndrome,” “epidemiology,” “incidence,” and “prevalence.” The materials selected were in English, Spanish, or Portuguese. Results. The titles of more than 1 000 potentially relevant articles were screened, and more than 600 selected abstracts were reviewed in detail. Twenty papers published from 1990 through 2004 were selected and analyzed. The studies described in the 20 articles were extremely heterogeneous in design, population, sample size, end points, and follow-up. The studies did not all apply the same clinical definition for sepsis, thus making it impossible to produce a precise overall estimate of the magnitude of the problem of sepsis in Latin America. Conclusions. The results of the literature review suggest that the clinical and epidemiological approaches to the problem of sepsis in Latin America have sometimes been inappropriate with respect to research design, study population, and clinical outcome. Further, some data suggest that in terms of both frequency and mortality the situation with sepsis and severe systemic infections may be worse in Latin America than it is in developed countries.